Workplace hazards and health among informally employed domestic workers in 14 cities, United States, 2011–2012: Using four approaches to characterize workers' patterns of exposures. Issue 12 (12th October 2022) - Wright, Emily; Chen, Jarvis T.; Beckfield, Jason; Theodore, Nik; Krieger, Nancy
Abstract: Background: We characterized informally employed US domestic workers' (DWers) exposure to patterns of workplace hazards, as well as to single hazards, and examined associations with DWers' work‐related and general health. Methods: We analyzed cross‐sectional data from the sole nationwide survey of informally employed US DWers with work‐related hazards data, conducted in 14 cities (2011–2012; N  = 2086). We characterized DWers' exposures using four approaches: single exposures ( n  = 19 hazards), composite exposure to hazards selected a priori, classification trees, and latent class analysis. We used city fixed effects regression to estimate the risk ratio (RR) of work‐related back injury, work‐related illness, and fair‐to‐poor self‐rated health associated with exposure as defined by each approach. Results: Across all four approaches—net of individual, household, and occupational characteristics, and city fixed effects—exposure to workplace hazards was associated with increased risk of the three health outcomes. For work‐related back injury, the estimated RR associated with heavy lifting (the single hazard with the largest RR), exposure to all three hazards selected a priori (worker did heavy lifting, climbed to clean, and worked long hours) versus none, exposure to the two hazards identified by classification trees (heavy lifting, verbally abused) versus "no heavy lifting, " and membership in the most‐ versus least‐exposed latent class were, respectively, 3.4 (95% confidence interval [CI] 2.7–4.1); 6.5 (95% CI 4.8–8.7); 4.4 (95% CI 3.6–5.3), and 6.6 (95% CI 4.6–9.4). Conclusions: Measures of joint work‐related exposures were more strongly associated than single exposures with informally employed US DWers' health profiles.